¿Existe aún la industria manufacturera en el Perú? - Cárdenas Núñez, Gilberto José Rafael (2009)
The manufacturing peruvian industry still exists. After many years in which the process of liberalization of the economy submitted to the industrial companies of the sector to the external competition(competence), it is possible to estimate that more than 110 thousand companies exist and produce. The principal ones are them of 10 to more workers, who produce more than 80% of the manufacturing national total, are principally in Lima and Callao, or in the capitales of the departments, it is a light(slight) industry little articulated to the natural resources of the country, of relatively intermediate technology and that largely of the national territory does not exist.